Effects of liraglutide on gastrointestinal functions and weight in obesity: A randomized clinical and pharmacogenomic trial. Issue 8 (27th July 2022) - Maselli, Daniel; Atieh, Jessica; Clark, Matthew M.; Eckert, Deborah; Taylor, Ann; Carlson, Paula; Burton, Duane D.; Busciglio, Irene; Harmsen, W. Scott; Vella, Adrian; Acosta, Andres; Camilleri, Michael
Abstract: Objective: This study aimed to determine the effects of a long‐acting glucagon‐like peptide‐1 (GLP‐1) receptor agonist, liraglutide, and placebo subcutaneously over 16 weeks on weight and gastric functions and to evaluate associations of single‐nucleotide polymorphisms in GLP1R (rs6923761) and TCF7L2 (rs7903146) with effects of liraglutide. Methods: The study conducted a randomized, parallel‐group, placebo‐controlled, 16‐week trial of liraglutide, escalated to 3 mg subcutaneously daily in 136 otherwise healthy adults with obesity. Weight, gastric emptying of solids (GES), gastric volumes, satiation, and body composition measured at baseline and after treatment were compared in two treatment groups using analysis of covariance. Results: Liraglutide ( n  = 59) and placebo ( n  = 65) groups completed treatment. Relative to placebo, liraglutide increased weight loss at 5 and 16 weeks (both p  < 0.05), slowed time to half GES (T1/2 ) at 5 and 16 weeks (both p  < 0.001), and increased fasting gastric volume ( p  = 0.01) and satiation ( p  < 0.01) at 16 weeks. GES T1/2 was positively correlated with weight loss on liraglutide (both p  < 0.001). After 16 weeks of liraglutide, GLP1R rs6923761 (AG/AA vs. GG) was associated with reduced percent body fat ( p  = 0.062), and TCF7L2 rs7903146 (CC vs. CT/TT) was associated with lower body weight ( p  = 0.015). Conclusions: Liraglutide, 3 mg, induces weight loss with delay in GES T1/2 and reduces calorie intake. Slowing GES and variations in GLP1R and TCF7L2 are associated with liraglutide effects in obesity.